Analysis of the Return and Risk of Investment in Insurance Companies Listed on the Indonesia Stock Exchange - Aizzah Sifaur Robbyah; Ferry Khusnul Mubarok; Rahman El Junusi; Rofiul Wahyudi (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2021)
The return and risk of stock investment have a high level of volatility because it depends on fundamental and technical conditions and the influence of micro and macro variables. This study aims to determine the risk and return on investment in insurance companies and analyze the effect of macroeconomic variables on the level of risk and return on investment in insurance companies. The sampling technique used was purposive sampling. Data analysis shows that for three years, Asuransi Jasa Tania Tbk has the highest level of conclusion, which is 22.3%, and Asuransi Harta Aman Pratama Tbk. has the lowest rate of -3.3%. For three years, the value of Gross Domestic Product has increased successively so that this will cause a stock return that is proportional to the level of risk that will be faced. Changes in the inflation rate up and down for three consecutive years have a different effect every year where when the inflation rate decreases, the rate of return on investment will be high. In addition, the interest rate decreased from 4.75% in 2016 to 4.25% in 2017. Then it increased to 6.00% in 2018. The Rupiah exchange rate against the dollar is getting weaker, indicating an increase in the exchange rate. Every year from 2016 to 2018. When the rupiah exchange rate weakens, people will choose to invest in foreign currencies because the value of these foreign currencies can determine the size of the risk of a business.